2019
DOI: 10.1089/neu.2018.5669
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Stimulation of Mitochondrial Biogenesis Using the Food and Drug Administration-Approved β2-Adrenoreceptor Agonist Formoterol for the Treatment of Spinal Cord Injury

Abstract: A hallmark of the progressive cascade of damage referred to as secondary spinal cord injury (SCI) is vascular disruption resulting in decreased oxygen delivery and loss of mitochondria homeostasis. While therapeutics targeting restoration of single facets of mitochondrial function have proven largely ineffective clinically post-SCI, comprehensively addressing mitochondrial function via pharmacological stimulation of mitochondrial biogenesis (MB) is an underexplored strategy. This study examined the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…While not directly investigated in the present study, the increase in markers of lipid metabolism observed in CSCI suggests that peripheral dopaminergic and adrenergic signalling pathways remain intact following a spinal injury or undergo adjustments to compensate for the lack of intact sympathetic control. Studies investigating the vasculature and skeletal muscle tissue following SCI partially corroborate this suggestion, with a similar vasoconstrictive response to infusion of an αadrenergic agonist in people with SCI compared with AB persons [24] and a maintained responsiveness to β-adrenergic agonists as evidenced by skeletal muscle hypertrophy after formoterol treatment in mice with SCI [25]. Moreover, a larger increase in blood pressure following noradrenaline administration in persons with CSCI (when compared with able-bodied individuals) has been reported, potentially resulting from hypersensitivity of α-adrenergic receptors in the vasculature [10].…”
Section: Discussionmentioning
confidence: 74%
“…While not directly investigated in the present study, the increase in markers of lipid metabolism observed in CSCI suggests that peripheral dopaminergic and adrenergic signalling pathways remain intact following a spinal injury or undergo adjustments to compensate for the lack of intact sympathetic control. Studies investigating the vasculature and skeletal muscle tissue following SCI partially corroborate this suggestion, with a similar vasoconstrictive response to infusion of an αadrenergic agonist in people with SCI compared with AB persons [24] and a maintained responsiveness to β-adrenergic agonists as evidenced by skeletal muscle hypertrophy after formoterol treatment in mice with SCI [25]. Moreover, a larger increase in blood pressure following noradrenaline administration in persons with CSCI (when compared with able-bodied individuals) has been reported, potentially resulting from hypersensitivity of α-adrenergic receptors in the vasculature [10].…”
Section: Discussionmentioning
confidence: 74%
“…The implications of this compensation, and if this increase in mRNA is truly translated into protein stills to be determined. In regards to a proposed increase in mitochondrial biogenesis by KD, KD increases mitochondrial mass in other neurological disorders such as epilepsy 64 and ischemic stroke 65 ; and recent publications highlight how mitochondrial biogenesis could be a potential pharmaceutical target to treat SCI 66,67 . VDAC1 has also been linked to an increase in the transcription of multiple ETS complexes by interacting with TOM20, a component of the receptor complex responsible for the recognition and translocation of cytosolically synthesized mitochondrial pre-proteins or enzymes required to promote the activation of the transcriptional machinery of the mitochondria 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the ADRB2 agonist can enhance the recovery in rats post-SCI (Zeman et al, 1999;Zeman et al, 2006;Brown et al, 2014). Scholpa et al (2019) performed using an FDA-approved compound with the ability to be repurposed, reinforcing the potential clinical applicability of their findings and demonstrating the pharmacological activation of ADRB2 receptor for the treatment of SCI. However, it seemed no previous studies that reported the association between PECAM1/LRP1 and SCI.…”
Section: Figure 9 |mentioning
confidence: 84%